PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH BERBASIS CAPCUT “MASUKNYA ISLAM DI PONOROGO DAN AKULTURASI BUDAYA” UNTUK SISWA KELAS X SMAN 1 BADEGAN - Rendi Miftahudin Fahmi; Najib Jauhari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The rapid development of this technology affects the quality of education in schools, especially in learning. Through available facilities such as smartphones, networks, projectors, and so on, teachers and students can collaborate learning activities with technology to create a climate of learning. teachers and students can collaborate learning activities with technology in order to create an effective learning climate. learning climate that is effective, efficient, and conducive learning climate. The lack of utilization of history learning media in class X SMAN 1 Badegan which is only limited to Power Point and PDF media, this is what encourages the use of history learning media. and PDF media, this is what encourages the conduct of this research. This research by developing learning media in the form of motion graphic videos based CapCut with the local history material of the entry of Islam in Ponorogo in the 15th century and the development of cultural acculturation in Ponorogo. The research method uses the Research and Development model of Sugiyono. The results of this study show that motion graphic videos as a history learning media has the potential to be applied. With a percentage of 92% for material experts and 80% for media experts. For media testing of students on a small group scale gets a percentage of 83% and for the large group 81%. From the results and validity test the motion graphic video learning media based on CapCut with material on the local history of the entry of Islam in Ponorogo in the 15th century and the development of cultural acculturation has the potential to beapplied in learning history class X SMAN 1 Badegan.